1997
DOI: 10.1021/jm970442u
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Field Analysis of A Series of Paclitaxel Analogues

Abstract: A series of 94 paclitaxel analogues exhibiting antitumor activity by promoting the assembly of microtubules and inhibiting the disassembly process of microtubules to tubulin were investigated using the comparative molecular field analysis (CoMFA) method. These compounds belonging to 10 structural classes were randomly divided into a training set of 80 compounds and a test set of 14 compounds. Since the three-dimension structure of ligand--receptor complex is unknown, from X-ray and NMR data we rationally selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…[166] In contrast, 7-OH is not as essential for the cytotoxicity of taxanes as 2′-OH but derivatives at 7-OH position are very stable under physiological conditions. [167, 168] As a result, derivatives of taxanes are almost always carried out at 2′-OH generating less toxic taxane prodrugs. Besides the improvement of drug encapsulation in lipid nano-carriers, taxane prodrugs have other advantages such as reduced systemic toxicity and potential of site-specific release of active drugs depending on the conjugation chemistry.…”
Section: Types Of Lipid-based Nanoparticles To Deliver Taxanesmentioning
confidence: 99%
“…[166] In contrast, 7-OH is not as essential for the cytotoxicity of taxanes as 2′-OH but derivatives at 7-OH position are very stable under physiological conditions. [167, 168] As a result, derivatives of taxanes are almost always carried out at 2′-OH generating less toxic taxane prodrugs. Besides the improvement of drug encapsulation in lipid nano-carriers, taxane prodrugs have other advantages such as reduced systemic toxicity and potential of site-specific release of active drugs depending on the conjugation chemistry.…”
Section: Types Of Lipid-based Nanoparticles To Deliver Taxanesmentioning
confidence: 99%
“…However, almost immediately it was realized that not all positions could be modified without reducing paclitaxel antitumor potency. In general, not only the taxane ring is necessary for activity, but also the N-acylated a-hydroxy-b-amino acid moiety [251,252]. Based on their SAR study, Ojima et al indicated that the C-3 0 phenyl group and 3 0 -N group can be replaced with other similar groups, the C-10 position can be modified with some acyl groups, and the C-2 position can be substituted [241].…”
Section: Paclitaxel and Its Derivativesmentioning
confidence: 99%
“…Paclitaxel prodrugs are usually designed by introducing a masking moiety to the C-2 0 position as this hydroxyl group seems to be required for cytotoxic effects [251,252]. Esters at this position can be synthesized selectively without protecting of the less reactive C-7 hydroxyl group.…”
Section: Paclitaxel and Its Derivativesmentioning
confidence: 99%
“…Additionally, according to the previous SAR studies on paclitaxel derivatives [75,76] as it is known that both N-acyl and free 2'-OH groups are required for taxoid activity [76], these prodrugs are not expected to be active themselves. This prodrug strategy was also applied for the design of a docetaxel (21) prodrug.…”
Section: Prodrugs Of Paclitaxel and Other Taxoidsmentioning
confidence: 99%